The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/aps.2015.67
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of microRNA and mRNA expression signatures in cancer

Abstract: Cancer is an extremely diverse and complex disease that results from various genetic and epigenetic changes such as DNA copy-number variations, mutations, and aberrant mRNA and/or protein expression caused by abnormal transcriptional regulation. The expression profiles of certain microRNAs (miRNAs) and messenger RNAs (mRNAs) are closely related to cancer progression stages. In the past few decades, DNA microarray and next-generation sequencing techniques have been widely applied to identify miRNA and mRNA sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 194 publications
(177 reference statements)
0
45
0
1
Order By: Relevance
“…MicroRNAs demonstrate exceptional stability even in difficult biological samples such as formalin-fixed paraffin-embedded tissue sections, blood, and urine [30, 31] and have been used as prognostic biomarkers in a number of cancers [32]. Moreover, several recent reports suggest that DCLK1 regulates EMT through a miRNA-dependent mechanism, which has also been confirmed in pancreatic and colon cancer using tumor xenograft models [25, 33].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs demonstrate exceptional stability even in difficult biological samples such as formalin-fixed paraffin-embedded tissue sections, blood, and urine [30, 31] and have been used as prognostic biomarkers in a number of cancers [32]. Moreover, several recent reports suggest that DCLK1 regulates EMT through a miRNA-dependent mechanism, which has also been confirmed in pancreatic and colon cancer using tumor xenograft models [25, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Ribonucleic acid (RNA) biomarkers comprising different coding and noncoding transcriptome such as messenger RNA (mRNA), microRNA (miRNA), and long noncoding RNA (lncRNA) are becoming progressively crucial in understanding disease diagnosis and prognosis due to their recognized physiological role in gene expression and regulation . Dysregulation of these RNA biomarkers is involved in the initiation and progression of several diseases including cancers .…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal expression of mRNAs has been widely demonstrated in human cancers, and researches suggested that the dysregulated mRNAs emerged as critical roles in various biological functions associated with progression of cancers. 27,28 However, only a few reports have identified mRNA profiles in T-cell lymphoma by microarray analysis. 16 In this study, we identified mRNAs in T-cell lymphomas from GEO database, which may be related to diagnosis, classification, medical treatment sensitivity, and tumor microenvironment in T-cell lymphomas.…”
Section: Discussionmentioning
confidence: 99%